2008
DOI: 10.4012/dmj.27.605
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distribution in Roots Restored with Different Types of Post Systems with Composite Resin

Abstract: Although composite resin core is used with various types of prefabricated posts, it remains unclear which kind of material is most suitable for the post. The aim of this study was to evaluate the influence of prefabricated posts on the stress distribution within the root by finite element analysis. Posts and cores were built up with composite resin and four types of prefabricated posts: two types of glass fiber posts (GFP1, GFP2) with low and high Young's moduli, a titanium post (TIP), and a stainless steel po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 35 publications
4
46
0
4
Order By: Relevance
“…Although the maximum von Mises stress values were not seemingly significantly different between the models with and without FRC posts, the more favourable distribution of maximum stresses in the models with posts could influence the longevity of the restoration over the years of use in intraoral conditions 4,9) . Numerous in vivo, in vitro and FEA studies have shown that the use of FRC posts and composite cores decreased the stresses in dental tissues 1,4,9,11,[28][29][30] . Certain clinical studies with a follow up period of 2 9) , 3 30) and 6 years 4) revealed a beneficial influence of fiber post insertion on the tooth survival in endodontically treated premolars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the maximum von Mises stress values were not seemingly significantly different between the models with and without FRC posts, the more favourable distribution of maximum stresses in the models with posts could influence the longevity of the restoration over the years of use in intraoral conditions 4,9) . Numerous in vivo, in vitro and FEA studies have shown that the use of FRC posts and composite cores decreased the stresses in dental tissues 1,4,9,11,[28][29][30] . Certain clinical studies with a follow up period of 2 9) , 3 30) and 6 years 4) revealed a beneficial influence of fiber post insertion on the tooth survival in endodontically treated premolars.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the adequate aesthetic and mechanical properties, and affordable price, it was shown that the direct resin composite fillings alone might not be sufficient to ensure the longevity of an endodontically treated tooth with an MOD cavity 8) . Therefore, additional procedures, such as the palatal and buccal cusp reduction (MODP, MODPB), and/or fiber-reinforced composite (FRC) posts [9][10][11][12][13] , were suggested. Both of these procedures entail removal of additional dental tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Hard resin and stainless steel were treated as elastic isotropic materials. The Young's modulus and Poissons' ratio, were set at 21 GPa and 0.27 17) , respectively, for hard resin and 200 GPa and 0.30 18) , respectively, for stainless steel.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…When the remaining tooth structure and alveolar bone mass are sufficient, the fracture resistances of teeth restored with cast posts and cores are comparatively high 12) . However, vertical root fractures are often seen in teeth restored with such restorations, caused by increased stress concentration at the end of the post because of the difference in Young's modulus between dentin and post materials [13][14][15] . When the restored teeth are used to retain fixed or removable partial dentures, larger stress is applied on abutment teeth than single crown restorations.…”
Section: Introductionmentioning
confidence: 99%